Odpowiedzi

2009-11-07T17:57:14+01:00
Wiadomo, że a + c = 10

Ciąg (a+2,b+5,c+4) jest arytmetyczny.

(a + 2) + (c + 4) = 2 * (b + 5)
a + c + 6 = 2 * b + 10
10 + 6 = 2 * b + 10
2 * b = 6
b = 3

Wiadomo także, że ciąg (a, b, c) jest geometryczny.
a * c = b²
a * c = 9

I jednocześnie a + c = 10, c = 10 - a

a * (10 - a) = 9
10a - a² = 9
a² - 10 a = -9
a² - 10 a + 9 = 0
(a - 9) * (a - 1) = 0
a = 9 lub a = 1
Jeśli a = 9 to c = 10 - 9 = 1.
Jeśli a = 1 to c = 10 - 1 = 9.

Odp. a = 1, b = 3, c = 9 albo a = 9, b = 3, c = 1.